Hetero-integration enables fast switching time-of-flight sensors for light detection and ranging - Park, Minseong; Baek, Yongmin; Dinare, Mesgana; Lee, Doeon; Park, Kyung Ho; Ahn, Jungho; Kim, Dahee; Medina, Joseff; Choi, Won Jin; Kim, Sihwan; Zhou, Changjie; Heo, Junseok; et al. (Scientific Reports, 2020)
The time-of-flight (ToF) principle is a method used to measure distance and construct three-dimensional (3D) images by detecting the time or the phase difference between emitted and back-reflected optical flux. The ToF principle has been employed for various applications including light ranging and detection (LiDAR), machine vision and biomedical engineering; however, bulky system size and slow switching speed have hindered the widespread application of ToF technology. To alleviate these issues, a demonstration of hetero-integration of GaN-based high electron mobility transistors (HEMTs) and GaAs-based vertical cavity surface emitting lasers (VCSELs) on a single platform via a cold-welding method was performed. The hetero-integrated ToF sensors show superior switching performance when compared to silicon-transistor-based systems, miniaturizing size and exhibiting stable ranging and high-resolution depth-imaging. This hetero-integrated system of dissimilar material-based high-performance devices suggests a new pathway towards enabling high-resolution 3D imaging and inspires broader range application of heterogeneously integrated electronics and optoelectronics.